2013
DOI: 10.1073/pnas.1217996110
|View full text |Cite
|
Sign up to set email alerts
|

Design of a superior cytokine antagonist for topical ophthalmic use

Abstract: IL-1 is a key inflammatory and immune mediator in many diseases, including dry-eye disease, and its inhibition is clinically efficacious in rheumatoid arthritis and cryopyrin-associated periodic syndromes. To treat ocular surface disease with a topical biotherapeutic, the uniqueness of the site necessitates consideration of the agent's size, target location, binding kinetics, and thermal stability. Here we chimerized two IL-1 receptor ligands, IL-1β and IL-1Ra, to create an optimized receptor antagonist, EBI-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 44 publications
6
65
0
Order By: Relevance
“…Our inability to create superior agonists and antagonists by creating chimeras of the putative binding sites for the D1/2 and D3 domains, in analogy to the strategy used for IL-1b and IL-1Ra (12), indicates that the IL-36 subfamily differs markedly from the IL-1 subfamily in the molecular mechanisms by which they activate and inhibit signaling. Through our mutational and loopswapping experiments, we observed that the affinity of both the agonist IL-36g (by mutation Ala 162 Asp) and the IL-36Ra (by loop swap of b4/5 from IL-36g) can be improved and, at least in the case of IL-36Ra, this also resulted in better antagonism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our inability to create superior agonists and antagonists by creating chimeras of the putative binding sites for the D1/2 and D3 domains, in analogy to the strategy used for IL-1b and IL-1Ra (12), indicates that the IL-36 subfamily differs markedly from the IL-1 subfamily in the molecular mechanisms by which they activate and inhibit signaling. Through our mutational and loopswapping experiments, we observed that the affinity of both the agonist IL-36g (by mutation Ala 162 Asp) and the IL-36Ra (by loop swap of b4/5 from IL-36g) can be improved and, at least in the case of IL-36Ra, this also resulted in better antagonism.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of superior agonists and antagonists chimeras is not directly adoptable from the IL-1b/IL-1Ra system. We created chimeras of IL36g and IL-36Ra in analogy to the superior agonistic and antagonistic IL-1b/IL-1Ra chimeras described by Hou et al (12). Chimera 125:30 corresponds to the superior agonist, chimera 96:63 to the superior antagonist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its potential relevance for the disease is highlighted by the clinical development of an IL-1 receptor antagonist for ocular surface inflammation, EBI-005. 30,31 Matrix metalloproteinase-9 is a protease that has been implicated in the breakage of tight junctions of corneal epithelium and in the corneal barrier disruption in desiccating stress. 8,32,33 Tear levels of MMP-9 have been shown to correlate with corneal staining intensity and other clinical parameters in dry eye patients.…”
Section: Discussionmentioning
confidence: 99%